Ovary Signals for Pollen Tube Guidance in Chalazogamous Mangifera indica L. - Lora, Jorge; Perez, Veronica; Herrero, Maria; Hormaza, Jose I. (Frontiers in Plant Science, 2021)
Most flowering plants show porogamy in which the pollen tubes reach the egg apparatus through the micropyle. However, several species show chalazogamy, an unusual pollen tube growth, in which the pollen tubes reach the embryo sac through the chalaza. While ovary signals for pollen tube growth and guidance have been extensively studied in porogamous species, few studies have addressed the process in chalazogamous species such as mango (Mangifera indica L.), one of the five most important fruit crops worldwide in terms of production. In this study, we characterize pollen-pistil interaction in mango, paying special attention to three key players known to be involved in the directional pollen tube growth of porogamous species such as starch, arabinogalactan proteins (AGPs) and Ɣ -aminobutyric acid (GABA). Starch grains were observed in the style and in the ponticulus at anthesis but their number decreased one day after anthesis. AGPs were homogenously observed in the style and ovary, but were more conspicuous in the nucellus around the egg apparatus. GABA was specifically observed in the transmitting tissue, including the ponticulus. Moreover, GABA was shown to stimulate in vitro mango pollen tube growth and elongation. The results support the heterotrophic growth of mango pollen tubes in the style at the expense of starch, similarly to the observations in porogamous species. However, unlike porogamous species, the micropyle of mango does not show high levels of GABA and starch, although they were observed in the ponticulus and could play a role in supporting the unusual pollen tube growth in chalazogamous species.